Olika mönster mellan genetisk variation och lokal anpassning hos tall - Miljövariabler och koordinater för varje population - Hall, David (Swedish National Data Service, 2021)
In this study, we sampled 54 Scots pine populations from the Norwegian coast over the Arctic Circle to western Russia covering 47.3 longitudes or more than 1/8th of the earth’s circumference, which represents the most comprehensive coverage of Northern Europe to date. We inferred variation in autumn phenology and dormancy progression from freeze hardiness tests conducted on >5000 seedlings, of which >900 seedlings from 24 populations were genotyped using genotyping-by-sequencing (GBS). Our main goal was to evaluate adaptive responses in Scots pine at phenotype and genotype levels. Evaluation of cold hardiness along environmental and geographical gradients would contribute to an understanding of the performance of these gradients for predicting freeze damage levels. The genotype data allow evaluation of genetic variance across landscapes and thus shed light on the degree of genetic-environmental association and the recolonization history of Scots pine in Scandinavia. Environmental variables for each population was extracted based on their latitude and longitude at origin from 68 different high resolution environmental grids. These variables were then used for phenotype- and genotype-environment association analyses. A description of all variables can be found in Table S2 in “Document S1. Supplemental methods, Supplemental Figures 1–4, and Supplemental Tables 1–6.”, available from doi.org/10.1016/j.xplc.2020.100139 I den här studien undersökte vi den lokala anpassningen av tidspunkten för invintring och den genetiska variationen hos naturligt tallbestånd i norra Europa. Det geografiska området av studien sträcker sig från Norge i väster till och Komi-regionen i västra Ryssland fram till Uralbergen. Drygt 5000 frön från 56 populationer såddes upp och utsattes för frystemperaturer för att skatta deras frosttolerans och variationen i egenskapen över det geografiska området av denna studie. Från 24 av dessa 56 populationer samlades barr för att extrahera DNA till genotypning för att också kvantifiera den ...